Treatment Effects of the Second-Generation Tyrosine Kinase Inhibitor Dasatinib on Autoimmune Arthritis - Guo, Kai; Bu, Xin; Yang, Chongfei; Cao, Xiaorui; Bian, Huan; Zhu, Qingsheng; Zhu, Jinyu; Zhang, Dawei (Frontiers in Immunology, 2019)
Rheumatoid arthritis (RA) is a multifactorial autoimmune disease that primarily manifests as persistent synovitis and progressive joint destruction. Imatinib exhibited a therapeutic effect in murine collagen-induced arthritis (CIA) via selective inhibition tyrosine kinases. The second-generation tyrosine kinase inhibitor dasatinib exhibits more durable hematological and cytogenetic effects and more potency compared to imatinib. However, the effect of dasatinib on CIA is poorly understood. The present study investigated the treatment effect of dasatinib on autoimmune arthritis. We demonstrated that dasatinib alleviated arthritis symptoms and histopathological destruction in CIA mice. Dasatinib treatment inhibited the production of proinflammatory cytokines including IL-1β, TNF-α, and IL-6, and promoted the production of the anti-inflammatory cytokine IL-10. Dasatinib treatment also suppressed the expression of anti-mouse CII antibodies including total IgG, IgG1, IgG2 and IgG2b, in CIA mice. We further demonstrated that dasatinib inhibited the migration and proliferation of fibroblast-like synoviocytes (FLS) from RA patients and promoted FLS apoptosis. The mRNA expression of MMP 13, VEGF, FGF and DDK1 was down-regulated in FLS treated with dasatinib. Our findings suggest that dasatinib exhibited treatment effects on CIA mice and that FLS are an important target cell of dasatinib treatment in autoimmune arthritis.